2020
DOI: 10.1002/jlb.3ab0320-547rr
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor valproic acid attenuates phospholipase Cγ2 and IgE-mediated mast cell activation

Abstract: Mast cell activation through the high‐affinity IgE receptor (FcεRI) plays a central role in allergic reactions. FcεRI‐mediated activation triggers multiple signaling pathways leading to degranulation and synthesis of different inflammatory mediators. IgE‐mediated mast cell activation can be modulated by different molecules, including several drugs. Herein, we investigated the immunomodulatory activity of the histone deacetylase inhibitor valproic acid (VPA) on IgE‐mediated mast cell activation. To this end, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…Although over 100 genes are now associated with ASD [ 4 ], neonatal exposure to environmental risk factors such as microbial pathogens or certain drugs (e.g., the neurotoxin, valproic acid [VPA] [ 5 ]), can also provoke ASD [ 6 , 7 ]. VPA induces broad abnormalities in genes that regulate cell cycle, cell wall biogenesis, DNA repair and ion homeostasis [ 8 , 9 ]. In fact, VPA has traditionally been prescribed to control epilepsy [ 10 ], or for treatment of psychiatric conditions, such as bipolar disorders, through its modulation of GABA neurotransmission [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although over 100 genes are now associated with ASD [ 4 ], neonatal exposure to environmental risk factors such as microbial pathogens or certain drugs (e.g., the neurotoxin, valproic acid [VPA] [ 5 ]), can also provoke ASD [ 6 , 7 ]. VPA induces broad abnormalities in genes that regulate cell cycle, cell wall biogenesis, DNA repair and ion homeostasis [ 8 , 9 ]. In fact, VPA has traditionally been prescribed to control epilepsy [ 10 ], or for treatment of psychiatric conditions, such as bipolar disorders, through its modulation of GABA neurotransmission [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The degranulation assay was carried out as described previously ( 31 ). Briefly, 2x10 5 BMMC/0.25 mL of complete medium were incubated with L.m at different MOI for 90 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The degranulation assay was carried out as described previously (31). Briefly, 2x10 5 Finally, the cells were washed and resuspended in 0.15 mL of Stain Buffer and analyzed by flow cytometry.…”
Section: Degranulation Assaymentioning
confidence: 99%
“…Recent structure-function studies suggested a unique ligand-transduction mechanism in MRGPRX family receptors, as they lack many of the canonical motifs associated with signaling and ligand recognition in family A G protein-coupled receptors (GPCRs) (28,29). Interestingly, allergic FcεRI-and pseudo-allergic pathways share the same signaling components further downstream, including extracellular signal-regulated kinase1/2 (ERK1/2), P38 and AKT, though kinetics differ between routes (26,(30)(31)(32). Both pathways also activate the guanosine triphosphatase (GTPase) Cdc42 upstream of actin cytoskeleton rearrangements, processes that involve the unconventional type I myosin 1f (MYO1F) (33).…”
Section: Introductionmentioning
confidence: 99%